Hannah Arendt and concentration camps. An image of hell (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article deals with Hannah Arendt´s work on Second World War concentration and extermination camps, which she considers the main institution of organized power. Her analysis focuses on concentration camps as life-size experiments on human beings’ lives, whereby it is made clear that anything can happen. This article highlights the author’s philosophical perspective on this subject, which presents these spaces of exception as involving a hiatus in the public sphere and therefore annihilating the possibility of political practice.
Keywords: Concentration camp; H. Arendt; Political philosophy; Totalitarianism